Selebritas dalam Pemilu 2019 - Wicaksono, Moddie Alvianto; Aziz, Muhammad Saiful (Universitas Brawijaya, 2020)
The 2019 election contest was over. The winner is known. An incumbent, Joko Widodo, who was paired with Ma'ruf Amin, was able to outperform his competitors Prabowo Subianto and Sandiaga Uno. Beside Jokowi-Ma'ruf Amin's victory, there is something interesting to look at. Namely, the decreasing number of celebrity electability in parliament. Does this further confirm that celebrities are not eligible? Does the level of celebrity popularity affect the level of electability in the 2019 elections? Does celebrity function more as celebrity endorsers? What is clear, celebrities to enter the political sphere need to be listened to and reconsidered. This research uses a qualitative research approach and is carried out with a period of April-May 2019. Data collection techniques using the study of literature that is looking for and sorting out references and secondary data. While the data analysis uses data presentation analysis. This research shows: 1) Celebrities are no longer the primary consideration of voters in elections, 2) Celebrity popularity is not directly proportional with celebrity electability, 3) Political parties have failed to implement the function of political recruitment.